An active feedback recovery technique from disruption events induced by m = 2, n = 1 tearing modes in ohmically heated tokamak plasmas. (30th March 2015) - Zanca, P.; Paccagnella, R.; Finotti, C.; Fassina, A.; Manduchi, G.; Cavazzana, R.; Franz, P.; Piron, C.; Piron, L.
Abstract: We present experimental results of magnetic feedback control on the m  = 2, n  = 1 tearing mode in RFX-mod operated as a circular ohmically heated tokamak. The feedback suppression of the non-resonant m  = 2, n  = 1 resistive wall mode (RWM) in q ( a ) < 2 plasmas is a well-established result of RFX-mod. The control of the tearing counterpart, which develops in q ( a ) > 2 equilibrium, is instead a more difficult issue. In fact, the disruption induced by a growing amplitude m  = 2, n  = 1 tearing mode can be prevented by feedback only when the resonant surface q  = 2 is close to the plasma edge, namely 2 <  q ( a ) < 2.5, and the electron density does not exceed approximately half of the Greenwald limit. The RFX-mod data show very clearly that a large amplitude m  = 2, n  = 1 tearing mode significantly limits the operative region of plasma parameters even in the presence of an efficient magnetic feedback. A combined technique of tearing mode and q ( a ) control has been therefore developed to recover the discharge from the most critical conditions: the potentially disruptive tearing mode is converted into the relatively benign RWM by suddenly decreasing q ( a ) below 2. The experiments successfully demonstrate the concept. The q ( a ) control has been performed through the plasma current, given the capability of the toroidal loop-voltage power supply of RFX-mod. We also propose a path for decreasing q ( a ) by acting on the plasma shape, which could be applied to medium size elongated tokamaks.